Biomarkers for SUDEP: Are We There Yet?. Issue 4 (July 2019) - King-Stephens, David
Postconvulsive Central Apnea as a Biomarker for Sudden Unexpected Death in Epilepsy (SUDEP) Laura Vilella, MD, Nuria Lacuey, MD, Johnson P. Hampson, MSBME, M. R. Sandhya Rani, PhD, Rup K. Sainju, MBBS, Daniel Friedman, MD, Maromi Nei, MD, Kingman Strohl, MD, Catherine Scott, MPhil, Brian K. Gehlbach, MD, Bilal Zonjy, MD, Norma J. Hupp, Anita Zaremba, BA, Nassim Shafiabadi, MD, Xiuhe Zhao, MD, Victoria Reick-Mitrisin, MS, Stephan Schuele, MD, MPH, Jennifer Ogren, PhD, Ronald M. Harper, PhD, Beate Diehl, MD, PhD, FRCP, Lisa Bateman, MD, Orrin Devinsky, MD, George B. Richerson, MD, PhD, Philippe Ryvlin, MD, PhD, and Samden D. Lhatoo, MD, FRCP. Neurology . 2019;92:e171-e182. Objective: To characterize peri-ictal apnea and postictal asystole in generalized convulsive seizures (GCS) of intractable epilepsy. Methods: This was a prospective, multicenter epilepsy monitoring study of autonomic and breathing biomarkers of sudden unexpected death in epilepsy (SUDEP) in patients ≥18 years old with intractable epilepsy and monitored GCS. Video electroencephalography, thoracoabdominal excursions, nasal airflow, capillary oxygen saturation, and electrocardiogram were analyzed. Results: We studied 148 GCS in 87 patients. Nineteen patients had generalized epilepsy, 65 had focal epilepsy, 1 had both, and the epileptogenic zone was unknown in 2. Ictal central apnea (ICA) preceded GCS in 49 (40.4%) of 121 seizures in 23 patients, all with focal epilepsy. Postconvulsive central apnea (PCCA) occurred in 31 (22.1%) of 140 seizures in 22 patients, with generalized, focal, or unknown epileptogenic zones. In 2 patients, PCCA occurred concurrently with asystole (near-SUDEP), with an incidence rate of 10.2 per 1000 patient-years. One patient with PCCA died of probable SUDEP during follow-up, suggesting a SUDEP incidence rate 5.1 per 1000 patient-years. No cases of laryngospasm were detected. Rhythmic muscle artifact synchronous with breathing was present in 75 of 147 seizures and related to stertorous breathing (odds ratio: 3.856, 95% confidence interval: 1.395-10.663, P = .009). Conclusions: Postconvulsive central apnea occurred in both focal and generalized epilepsies, suggesting a different pathophysiology from ICA, which occurred only in focal epilepsy. Postconvulsive central apnea was seen in 2 near-SUDEP cases and 1 probable SUDEP case, suggesting that this phenomenon may serve as a clinical biomarker of SUDEP. Larger studies are needed to validate this observation. Rhythmic postictal muscle artifact is suggestive of post-GCS breathing effort rather than a specific biomarker of laryngospasm. : Hypoxemia Following Generalized Convulsive Seizures: Risk Factors and Effect of Oxygen Therapy Sylvain Rheims, MD, PhD, Blanca Mercedes Alvarez, MD, Veriano Alexandre, MD, PhD, Jonathan Curot, MD, Louis Maillard, MD, PhD, Fabrice Bartolomei, MD, PhD, Philippe Derambure, MD, PhD, Edouard Hirsch, MD, PhD, V´eronique Michel, MD, Francine Chassoux, MD, PhD, Didier Tourniaire, MD, Arielle Crespel, MD, Arnaud Biraben, MD, Vincent Navarro, MD, PhD, Philippe Kahane, MD, PhD, Bertrand De Toffol, MD, PhD, Pierre Thomas, MD, PhD, Sarah Rosenberg, MD, PhD, Luc Valton, MD, PhD, Laurent Bezin, PhD, and Philippe Ryvlin, MD, PhD, on behalf of the REPO2MSE Study Group. Neurology . 2019;92:e183-e193. Objective: To analyze the factors that determine the occurrence or severity of postictal hypoxemia in the immediate aftermath of a generalized convulsive seizure (GCS). Methods: We reviewed the video electroencephalography (EEG) recordings of 1006 patients with drug-resistant focal epilepsy included in the REPO2MSE study to identify those with ≥1 GCS and pulse oximetry (SpO2 ) measurement. Factors determining recovery of SpO2 ≥ 90% were investigated using Cox proportional hazards models. Association between SpO2 nadir and person- or seizure-specific variables was analyzed after correction for individual effects and the varying number of seizures. Results: A total of 107 GCS in 73 patients were analyzed. A transient hypoxemia was observed in 92 (86%) GCS. Rate of GCS with SpO2 < 70% dropped from 40% to 21% when oxygen was administered early ( P = .046). Early recovery of SpO2 ≥ 90% was associated with early administration of oxygen ( P = .004), absence of postictal generalized EEG suppression (PGES; P = .014), and extratemporal lobe epilepsy ( P = .001). Lack of early administration of O2 ( P = .003), occurrence of PGES ( P = .018), and occurrence of ictal hypoxemia during the focal phase ( P = .022) were associated with lower SpO2 nadir. Conclusion: Postictal hypoxemia was observed in the immediate aftermath of nearly all GCS, but administration of oxygen had a strong preventive effect. Severity of postictal hypoxemia was greater in temporal lobe epilepsy and when hypoxemia was already observed before the onset of secondary GCS.